Survivorship and Growth Performance of Red Spiny Lobster Panulirus longipes longipes Reared in Floating Netcages Fed with Sardinella spp at Different Feeding Rates - Becira, Joel G; Orcajada, Marivel (Science Diliman: A Journal of Pure and Applied Sciences; Vol 18 No 1 (2006), 2007)
This study was conducted to determine the survivorship and growth performance of Panulirus longipes longipes fed with Sardinella spp. in floating netcages at different feeding rates and to determine which feeding rate provides the best feed conversion ratio. Results showed that a feeding rate of 20% gave the highest growth (final average weight) followed by 15% and 10% feeding rates, respectively. In terms of length increment, 20% feeding rate likewise promoted the highest increment. Differences in feed conversion ratio among treatments was significant (P<0.05). Among the different treatments however, stocks fed at 15% body weight attained better growth increment and trend in feed conversion ratio.